2021
DOI: 10.1016/j.diabet.2020.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 pandemic lockdown on gestational diabetes mellitus: A retrospective study

Abstract: Objective The objective of our study was to evaluate the impact of the lockdown period on the glycemic balance in patients with GDM. Methods A retrospective study in one center (Lille, France) compared two periods: the COVID-19 lockdown of 18 March 2020 to 7 May 2020 versus the same period during 2019. Glucose targets were defined by a capillary fasting glucose target < 5.1mmol/L and/or a 2-hour postprandial capillary glucose < 6.6 mmol/L. GDM control was defined as: go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 4 publications
5
65
1
3
Order By: Relevance
“…Raise in HbA1c was a similar result to earlier studies that Verma et al found in type 1 diabetes patients. A similar result from France, including a comparison between gestational diabetes patients from 2019 to 2020 showed lower diabetes control in pandemic lockdown [ 10 ]. As easily suspected, several factors can have been responsible for increasing blood glucose and lipid levels.…”
Section: Discussionmentioning
confidence: 66%
“…Raise in HbA1c was a similar result to earlier studies that Verma et al found in type 1 diabetes patients. A similar result from France, including a comparison between gestational diabetes patients from 2019 to 2020 showed lower diabetes control in pandemic lockdown [ 10 ]. As easily suspected, several factors can have been responsible for increasing blood glucose and lipid levels.…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, some patients required additional medications to control blood glucose levels during lockdown [ 57 ]. In women with GDM, the use of insulin therapy was significantly higher in 2020 (47.7%) compared with 2019 (36.2%) [ 58 ]. These results were explained by anxiety, dietary habits, and reduced physical activity [ 58 ].…”
Section: Lockdown Lifestyle and Diabesity: Implications For Pregnmentioning
confidence: 99%
“…In women with GDM, the use of insulin therapy was significantly higher in 2020 (47.7%) compared with 2019 (36.2%) [ 58 ]. These results were explained by anxiety, dietary habits, and reduced physical activity [ 58 ]. In France, a higher rate of poor postprandial glycemic control was observed during the COVID-19 lockdown from 18 March 2020 to 7 May 2020 (13.7%), as compared with the same period during 2019 (8.7%) [ 58 ].…”
Section: Lockdown Lifestyle and Diabesity: Implications For Pregnmentioning
confidence: 99%
See 1 more Smart Citation
“… Gestational diabetes with/without COVID -19 infection: This issue has been less researched. As shown for patients with type 2 diabetes, lockdown during COVID-19 could lead to worsening of glycemia ( 32 ). In a meta-analysis 128176 non-pregnant patients (228 studies) and 10000 pregnant patients (121 studies) with confirmed COVID-19 were included.…”
Section: Introductionmentioning
confidence: 99%